2006
DOI: 10.1007/bf02931615
|View full text |Cite
|
Sign up to set email alerts
|

Activity of translation system and abundance of tmRNA during development ofStreptomyces aureofaciens producing tetracycline

Abstract: Transition from exponential phase of growth to stationary phase in Streptomyces aureofaciens is characterized by a decrease in the rate of translation and induction of tetracycline (Ttc) biosynthesis. In exponential phase, no significant changes were found in the activity of ribosomes at binding of ternary complex Phe-tRNA.EF-Tu.GTP to the A-site on ribosomes. Overexpression of Ttc in stationary phase is accompanied by a decrease in the binding of the ternary complex Phe-tRNA.EF-Tu.GTP to the A-site of ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…The change in ssrA promoter activity suggested that the increased synthesis and levels of tmRNA were an adaptive response to ribosome inhibition. Clearly, this expands on previous studies on the effect of ribosome inhibitors on tmRNA levels in other bacteria (Montero et al , 2006; Paleckova et al , 2006). To our knowledge, this is the first direct study of tmRNA in mycobacteria.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The change in ssrA promoter activity suggested that the increased synthesis and levels of tmRNA were an adaptive response to ribosome inhibition. Clearly, this expands on previous studies on the effect of ribosome inhibitors on tmRNA levels in other bacteria (Montero et al , 2006; Paleckova et al , 2006). To our knowledge, this is the first direct study of tmRNA in mycobacteria.…”
Section: Discussionsupporting
confidence: 74%
“…Increased tmRNA levels were described previously for other bacteria exposed to antimicrobial agents. Montero et al (2006) reported that chloramphenicol increased tmRNA levels up to 40‐fold in the extremophile T. maritima , and Paleckova et al (2006) reported that streptomycin increased tmRNA levels by 2.6‐fold in S. aureofaciens . However, it was not clear from these studies whether the increased tmRNA levels were the result of increased tmRNA synthesis or of a reduction in tmRNA degradation, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main chaperone and stress control protein DnaK Hsp70 links to reduced growth rates and heat‐shock sensitivity (Wickner et al , 1991; Bucca et al , 2003; Guisbert et al , 2004), the drug‐resistance regulators, TipA and UspA, to antibiotic sensitivity (Nystrom & Neidhardt, 1992; Kahmann et al , 2003), the cell‐division activator SsgA and its specific transcriptional activator SsgR to developmental defects (van Wezel et al , 2000; Traag et al , 2004; Noens et al , 2007), the alternative translation factor EF‐Tu3 to nutrient stress (van Wezel et al , 1995) and the global transcriptional regulator and nutrient sensory DasR to oxidative stress, programmed cell death and antibiotic production (Rigali et al , 2006, 2008). Transcription of tmRNA is possibly induced by oxidative stress (Paget et al , 2001) in S. coelicolor , as are dnaK, tipA and dasR (Paget et al , 2001; Paleckova et al , 2006; S.B., B.A.T. and G.P.v W., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the ultimate stress response is development; after nutrient depletion, the underlying vegetative mycelium or substrate mycelium is degraded autolytically to yield the necessary building blocks for the aerial mycelium and spores. Several studies have suggested a function of tmRNA in stress control, such as oxidative stress, heat shock and exposure to antibiotics, although the mechanisms and triggers have not been uncovered (Paget et al , 2001; Braud et al , 2006; Paleckova et al , 2006; Yang & Glover, 2009). In this study, we show that in streptomycetes, specific control of gene expression is the main role of tmRNA, with tmRNA‐mediated trans ‐translation tagging almost exclusively the main stress or developmental proteins, which suggests that tmRNA‐mediated protein tagging has evolved into a specialized translational control system in these organisms.…”
Section: Introductionmentioning
confidence: 99%